Model Sistem Dinamis Ketersediaan Air PDAM Cilegon Mandiri - Saputro, Muhammad Rifki; Noor, Firmansyah Muhammad; Maulana, Rifan Nur; Sahrupi (Universitas Muhammadiyah Sorong, 2024)
Cilegon Mandiri Regional Water Company is a regional government-owned enterprise responsible for providing water supply services to the community, managing water resources, producing clean water, and distributing it to the public. In ensuring the availability of clean water services, PDAM Cilegon Mandiri faces challenges in sustainable water resource management. The objective of this research is to develop a dynamic system model related to the availability of clean water in the Cilegon Mandiri Regional Water Company. The method used in this research is a qualitative-based dynamic system, which is a method used to form the structure, predict behavior, and provide feedback in a system. In modeling a system, dynamic systems require tools to illustrate the interdependencies among system elements, manifested in the form of a Causal Loop Diagram (CLD). The research results identify 14 variables that significantly influence the availability of clean water in PDAM Cilegon Mandiri. There is one reinforcing feedback loop as positive feedback that creates a growth pattern, and two balancing loops as positive feedback related to the improvement of water availability in PDAM Cilegon Mandiri. Although the Causal Loop Diagram approach has helped identify aspects in the clean water availability system, it is recommended to continue with a real simulation model to address real issues in the dynamic system of water availability in PDAM Cilegon Mandiri.